FAKTOR VIRULENSI ASPERGILLUS NIGER DAN CANDIDA ALBICANS: VIRULENCE FACTOR OF ASPERGILLUS NIGER AND CANDIDA ALBICANS - Basri Gani; Zinatul Hayati; Abdil lah Imron Nasution; Cut Soraya; Darniati (Dentika: Dental Journal, 2011)
Oral and respiratory diseases have been related with the fungal infections like oral candidiasis caused by Candida albicans and chronic rhinitis caused by Aspergillus niger. Both of these micr oorganisms are including in flora normal in the oral and nasal cavity. Aspergillus niger is rarely reported as aeroalergen in allergy rhinitis cases, but in chronic rhinitis its fungals are A. flavus and A. fumingatus. The aim of this study was to analyze the risk factors that influencing rhinitis and oral candidiasis and its relation. This research used rhinitis mucous identified various fungal used pour plate method.And then, cultured with SDA medium (Sabauraud's Dextrose Agar) to identify fung als morphology usedcultured slide.The results showed that Aspergillus niger was found more dominant than A. fumingatus and A. flavus in chronic rhinitis.In conclusion, Aspergillus niger was proved as an aeroallergen had had an important role in chronic rhinitis a nd could trigger the growth of Candida albicans.